Pathways Through Writing Blocks in the Academic Environment - Evans, Kate.; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2013)
Writing blocks are likely to strike any writer, even experienced ones, at sometime or another. Academia has its own challenges which can provoke blocks particular to that environment. Drawing on her knowledge as writer, psychotherapeutic counsellor and university tutor, Kate Evans has put together a book which addresses many of the differing aspects of writing blocks, including looking at their emotional and psychological foundations. With discussion and practical exercises, this volume suggests that an infusion of creative techniques can offer pathways through writing blocks in the academic environment. The case studies provide an in-depth consideration of varying experiences of writing blocks. The book is aimed at students with essays, projects or reports to write, or theses to tackle; as well as academics who are working on articles and books. It will also offer insights for supervisors who wish to support those who are writing and guidance for people running writing groups within academia. Over-all the book encourages a creative, collaborative approach which aims to equip academics for writing within the context of the twenty-first century. (3z(BThis book offers something for every academic writer, whether budding or experienced. Students struggling with essays and dissertations will find many practical exercises along with invaluable advice. More practised writers will encounter fresh insights$1! =(B. I am confident that you, the reader, will enjoy this book, which is itself a model of good writing.(3y (BDr Linda Finlay, the Open University, UK.s
Keywords: Education; Education; Education (general).